Devising a competency‐based continuing professional development programme to meet the needs of on‐call consultant paediatricians. (20th December 2013) - Wekell, Per; Aspegren, Knut; Holmgren, Daniel
Abstract Aim To define the clinical competencies currently required by on‐call consultant paediatricians in Sweden and to describe how these competencies can be acquired by using an outcome‐based continuing professional development (CPD) programme. Methods The overall aims and objectives of the programme were formulated to meet the current responsibilities of an on‐call consultant. It was delineated during a precourse needs assessment of 26 consultants, before being implemented with 16 participants, using a variety of learning, assessment and evaluation methods. Results The precourse needs assessment identified 217 clinical situations and 17 themes, and 139 subthemes were developed. During the programme evaluation, carried out using a reflective questionnaire, participants stated that they had improved their understanding of the role of, and demands on, the on‐call consultant. They had also felt more confident on‐call, had built a network of colleagues and updated their knowledge in relevant fields. Conclusion We defined and implemented a competency‐based CPD programme to meet the changing demands faced by on‐call consultant paediatricians. The aims and objectives of the programme were formulated according to a needs assessment among consultant paediatricians active in on‐call services. Evaluation of the programme indicates that participants moved in the direction of the overall objectives.